Implementation of an electronic genomic and family health history tool in primary prenatal care. Issue 1 (10th March 2014) - Edelman, Emily A.; Lin, Bruce K.; Doksum, Teresa; Drohan, Brian; Edelson, Vaughn; Dolan, Siobhan M.; Hughes, Kevin S.; O'Leary, James; Galvin, Shelley L.; DeGroat, Nicole; Pardanani, Setul; Feero, W. Gregory; et al.
<x xml:space="preserve">Abstract</x> "The Pregnancy and Health Profile, " (PHP) is a free genetic risk assessment software tool for primary prenatal providers that collects patient‐entered family (FHH), personal, and obstetrical health history, performs risk assessment, and presents the provider with clinical decision support during the prenatal encounter. The tool is freely available for download at www.hughesriskapps.net. We evaluated the implementation of PHP in four geographically diverse clinical sites. Retrospective chart reviews were conducted for patients seen prior to the study period and for patients who used the PHP to collect data on documentation of FHH, discussion of cystic fibrosis (CF) and hemoglobinopathy (HB) carrier screening, and CF and HB interventions (tests, referrals). Five hundred pre‐implementation phase and 618 implementation phase charts were reviewed. Documentation of a 3‐generation FHH or pedigree improved at three sites; patient race/ethnicity at three sites, father of the baby (FOB) race/ethnicity at all sites, and ancestry for the patient and FOB at three sites (P < 0.001–0001). CF counseling improved for implementation phase patients at one site (8% vs. 48%, P < 0.0001) and CF screening/referrals at two (2% vs. 14%, P < 0.0001; 6% vs. 14%; P = 0.05). Counseling and intervention rates did not increase for HB. This preliminary study suggests that the PHP can improve documentation of FHH, race, and ancestry, as well as the compliance with current CF counseling and intervention guidelines in some prenatal clinics. Future evaluation of the PHP should include testing in a larger number of clinical environments, assessment of additional performance measures, and evaluation of the system's overall clinical utility. © 2014 Wiley Periodicals, Inc.